Possible antidepressant mechanism of acupuncture: targeting neuroplasticity - Xu, Ning; He, Yue; Wei, Yong-Nan; Bai, Lu; Wang, Long (Frontiers in Neuroscience, 2025)
Major depressive disorder (MDD) is a highly prevalent and severely disabling psychiatric disorder that decreases quality of life and imposes substantial economic burden. Acupuncture has emerged as an effective adjunctive treatment for depression, it regulates neurotransmitters involved in mood regulation and modulates the activity of specific brain regions associated with emotional processing, as evidenced by neuroimaging and biochemical studies. Despite these insights, the precise neuroplastic mechanisms through which acupuncture exerts its antidepressant effects remain not fully elucidated. This review aims to summarize the current knowledge on acupuncture’s modulation of neuroplasticity in depression, with a focus on the neuroplasticity-based targets associated with acupuncture’s antidepressant effects. We encapsulate two decades of research into the neurobiological mechanisms underpinning the efficacy of acupuncture in treating depression. Additionally, we detail the acupoints and electroacupuncture parameters used in the treatment of depression to better serve clinical application.